Disulfide-stabilized recombinant MHC class I molecules allow the generation of peptide-receptive MHC tetramers. (October 2022) - Anjanappa, Raghavendra; Moritz, Andreas; Saikia, Ankur; Saini, Sunil Kumar; Garcia-Alai, Maria; Meijers, Rob; Rammensee, Hans-Georg; Hadrup, Sine Reker; Maurer, Dominik; Springer, Sebastian
Abstract : The F pocket region of MHC class I molecules is highly flexible in the absence of peptides, leading to instability and denaturation. We present here the stabilization of class I molecules by a disulfide bond between residules 84 and 139. Disulfide-stabilized class I molecules can be folded in vitro with the help of small molecules with very low affinity such as dipeptides. Once the small molecules are removed, folded disulfide-stabilized class I molecules bind exogenous peptide rapidly and stoichiometrically. This allows for the production of peptide-free MHC multimers that may be converted into the desired peptide complex within minutes. Crystal structures, binding affinity measurements, and staining data show equivalence of TCR binding to wild type class I. The stabilization is principally accessible for all class I allotypes.